Primer registro del zorrillo manchado del sur Spilogale angustifrons Howell 1902 para el estado de Campeche, México - Martínez-Kú, Diego Humberto; Escalona-Segura, Griselda; Vargas-Contreras, Jorge A. (Instituto de Ecología, A.C., 2007)
We found two roadside-killed individuals of Southern Spotted Skunk Spilogale angustifrons in the Calakmul region Campeche, Mexico (one, on the road Dziblachén-Xpujil, and the other, on the road to Calakmul archeological site). This information represents the first record for this species in this Mexican state and the extension of its distributional range.